MEMBANGUN KEPUASAN PELANGGAN MELALUI KUALITAS PELAYANAN PADA PT. PLN (PERSERO) RANTING WAY JEPARA LAMPUNG TIMUR - Sugiono, Sugiono (Fakultas Ekonomi UM Metro, 1978)
AbstractÂ The success of a company depends on the ability of a product or service to give satisfaction to the consumer. Moreover, if the company is engaged in the service, customer satisfaction is a necessary condition for their survival. As a State-Owned Enterprises (SOEs), PT. PLN. (Persero) is not only in demand to get high profit but must be able to provide excellent service in order to satisfy subscriber. This study aims to: How is the level of customer satisfaction to service quality and Level of the importance from each item and dimension from service quality which was gived by PT. PLN (Persero) branch of Way Jepara. From the analysis conducted using the Customer Satisfaction Index (CSI) obtained the value of 61%. This suggests that the level of consumer satisfaction in the category quite satisfied. Similarly, from the analysis using the Importance Performance Analysis (IPA) there are 8 (eight) items entering quadrant A, which means the expectations of these items are high but given the low kenerja. Quadrant B shows the items that are important to customers and has been implemented properly by the management of PT. PLN (Persero), but no one items that are entered in the quadrant. Quadrant C shows the items that have performance and low expectations and no one items that goes on the quadrant. While 6 items entered in quadrant D, Quadrant D shows the items were deemed less important by the customers, but its performance is done so well that customers assess the performance of the perceived excessive.Â Keywords: Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA)